Analysis of Antecedent Factors Influencing the Adoption and Conversion of Two-Wheeled Battery Electric Vehicles (BEVs) in East Kalimantan Province - Harits, Dimaz; Ismail Kurnia, Wahyu; Aji Wibowo, Nugroho (Universitas Ahmad Dahlan, 2025)
The rise in motorcycle ownership in Indonesia has increased energy consumption and greenhouse gas emissions, challenging the country's net-zero target by 2060. To mitigate this, the government is promoting the adoption and conversion of two-wheeled Battery Electric Vehicles (BEVs), but implementation remains below target, implying behavioral factors as a major barrier. This study analyzes the determinants influencing consumer and potential consumer behavior in adopting two-wheeled BEVs in East Kalimantan, a strategic region supporting the Indonesian Capital City. Using the Field Theory framework, the model integrates the Theory of Planned Behavior (TPB), which represents personal factors (Attitude, Subjective Norm, Perceived Behavioral Control, and Intention), and the Electric Vehicle Ecosystem (EVE), which represents environmental factors (Performance, Infrastructure, Price, and Features). Data from 400 respondents were analyzed using SEM-PLS, which explained 65.8% of the variance in adoption intention. The results show that Subjective Norms, Perceived Behavioral Control, Performance, Price, and Features significantly influence intention, while Attitude and Infrastructure do not. These findings reveal that consumers view two-wheeled BEVs primarily as functional alternatives to conventional motorcycles, rather than as environmentally friendly innovations. The contributes of this study is that it extends behavioral research by integrating TPB and EVE into Field Theory, and, practically, it highlights the need for policies that combine economic incentives with behavioral interventions to accelerate BEV adoption in Indonesia.